Ù…Ø´ÙƒÙ„Ø§Øª ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ¹Ù„Ø§Ø¬Ù‡Ø§ ÙÙŠ Ø¨Ø±Ù†Ø§Ù…Ø¬ Ø§Ù„Ø¥Ø¹Ø¯Ø§Ø¯ Ø§Ù„Ù„ØºÙˆÙŠ Ø¨Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¹Ø§Ù„ÙŠ Ù„Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙˆØ§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ù…ÙƒØ³Ø± - Mahmuddin, Ronny; Chamdar Nur; Andi Hawariah; Zulfiah Sam (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This research aims to describe the problem of teaching Arabic and its solutions in Language Preparation Program at STIBA Makassar. This type of research is descriptive qualitative research with the type of field research research conducted at the STIBA Makassar campus in the Language Preparation Program. Data collection uses in-depth interview methods by making 17 lecturers (male and female) in the Language Preparation Program and 4 students in charge of language as a source of data/informants. The results showed that: (1) Lecturer perception related to the problem of Arabic Language Teaching in Language Preparation Program at STIBA Makassar there are six, as follows: (a) Teaching Book; most informants state that some teaching books are irrelevant to the student's condition in terms of vocabulary and expressions or environmental culture. (b) Learners; most informants state that most students have low motivation and interest in learning Arabic and discipline in the application of language, (c) Facilities and Infrastructure; learning facilities and infrastructure are still minimal, such as the absence of language laboratories, (d) Evaluation; some informants highlighted that oral test instruments have not been applied to all language courses in the Midterm Examination (UTS) and in the Final Semester Examination (UAS), (e) Curriculum; most informants say that one year's learning is relatively short coupled with a large amount of teaching material, and (f) Environment; most informants mention that lecturers and senior students cannot yet be used as role models in language, and activities outside the classroom are not more oriented towards language improvement; (2) Lecturer's Perception regarding Solutions to the problems of teaching Arabic in Language Preparation Program at STIBA Makassar there are six, as follows: (a) Teaching Book; most informants state that the Language Preparation Program at STIBA Makassar needs to make some teaching books to adjust to the conditions of students, (b) Learners; all informants say that the solution in overcoming the constraints of learners is the provision of motivation to students. Lecturers and senior students should be role models in the application of the language, (c) Facilities and Infrastructure; all informants state that STIBA Makassar should utilize learning facilities, namely language laboratories, (d) Evaluation; the infroman states that oral tests are important for the effectiveness of learning evaluation in all language courses at UTS and UAS, (e) Curriculum; all informants say that ideally language learning in the Language Preparation Program at STIBA Makassar is two years; (f) Environment; all informants say that the activation of language activities must be followed up by STIBA Makassar. Activities that do not synergize with language improvement must be reduced and the application of language rules. The implication of this research is that there is expected to be a follow-up to this study that highlights in terms of student perception related to constraints/problems in Arabic language learning and its solutions in Language Preparation Program at STIBA Makassar.